The Symbolic Meaning of the Jasmine Ronce Necklace in the Film "Jumbo" (2025): Roland Barthes' Semiotic Analysis - Nur Afni Rachman; Peni Arianita Wardani; Muhamad Farhan (Journal of English in Academic and Professional Communication, 2026)
Film, in its narrowest definition, refers to the presentation of images on a large screen; however, in a broader context, it may also encompass those broadcast on television. As a mass medium, film is a complex form of audiovisual art. This study employs Roland Barthes' semiotic approach to explore the symbolic significance of the jasmine ronce necklace in Ryan Adriandy's film "Jumbo." The analysis is conducted through two levels: denotation and connotation, along with the concept of myth. The jasmine ronce necklace is interpreted not merely as a physical object but as a cultural and ideological signifier. Findings from this study reveal that the jasmine ronce necklace embodies spiritual meaning, the sanctity of love, and emotional depth, which together construct cultural myths within the Indonesian context.